A review of the Iranian species of the family Onychiuridae (Collembola, Poduromorpha), with description of five new species from Hyrcanian Forests in Iran - Yahyapour, Eliye; Shayanmehr, Masoumeh; Vafaei-Shoushtari, Reza; Arbea, Javier I. (Zootaxa, 2020)
Five new species from different tribes of the family Onychiuridae, namely Heteraphorura kaprusi sp. nov. (Hymenaphorurini), Deuteraphorura dashtenazensis sp. nov. and Onychiuroides mazandaranensis sp. nov. (Onychiurini), Protaphorura hyrcanica sp. nov. and P. iranica sp. nov. (Protaphorurini), from different Caspian Hyrcanian Mixed Forests in the Northern Iranian province of Mazandaran are described and illustrated. H. kaprusi sp. nov. belongs to the oriental species-group of the genus characterized by granulated vesicles in PAO, D. dashtenazensis sp. nov.—to the group of Deuteraphorura species with 1+1 pso on Th. I, and with 3+3 pso on the posterior part of head and Th. II–Abd. III tergites, O. mazandaranensis sp. nov.—to the group of Onychiuroides with 4 papillae and 5 chaetae on AIIIO, P. hyrcanica sp. nov. and P. iranica sp. nov.—to the group of Protaphorura species with 3 pso on Ant. base, 2+2 pso on Th. II and subcoxae 1 of legs II–III without pso. In addition two other species have been found in the same forests: Protaphorura sakatoi (Yosii, 1966) and Protaphorura golestanica Kaprus’, Shayanmehr & Kahrarian, 2017 (second record of the species). An identification key of the 30 species of Onychiuridae recorded so far from Iran is given.